2020
DOI: 10.21203/rs.3.rs-31448/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Companion-Intensive Multi-aspect Weight Management in Chinese Adults with Obesity: A Six-Month Multicenter Randomized Clinical Trial

Abstract: Background: Obesity is a globally increasing health epidemic requiring early lifestyle intervention. Our main objective was to examine the effectiveness of companion-intensive multi-aspect weight management (CIMWM) in Chinese adults with obesity.Methods: In this 6-month, prospective, open-label, multicenter, randomized controlled clinical trial, we recruited 272 obese adults aged 18–50 years with a body mass index (BMI) ≥28.0 kg/m2 and capable of using smartphones. CIMWM (n=136) offered both daily online instr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Following the publication of the original article [ 1 ], the authors identified that the symbol of equal contribution is missing for the authors Wanzi Jiang, Shushu Huang, Shuai Ma, and Lei Chen.…”
Section: Correction To: Jiang Et Al Nutr Metab (Lond) (2021) 18:17 mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that the symbol of equal contribution is missing for the authors Wanzi Jiang, Shushu Huang, Shuai Ma, and Lei Chen.…”
Section: Correction To: Jiang Et Al Nutr Metab (Lond) (2021) 18:17 mentioning
confidence: 99%